Induction of interferon-stimulated genes and cellular stress pathways by morpholinos in zebrafish - Lai, J.K.H.; Gagalova, Kristina; Kuenne, C.; El-Brolosy, M.A.; Stainier, D.Y.R. (2019)
The phenotypes caused by morpholino-mediated interference of gene function in zebrafish are often not observed in the corresponding mutant(s). We took advantage of the availability of a relatively large collection of transcriptomic datasets to identify common signatures that characterize morpholino-injected animals (morphants). In addition to the previously reported activation of tp53 expression, we observed increased expression of the interferon-stimulated genes (ISGs), isg15 and isg20, the cell death pathway gene casp8, and other cellular stress response genes including phlda3, mdm2 and gadd45aa. Studies involving segmentation stage embryos were more likely to show upregulation of these genes. We also found that the expression of these genes could be upregulated by increasing doses of an egfl7 morpholino, or even high doses of the standard control morpholino. Thus, these data show that morpholinos can induce the expression of ISGs in zebrafish embryos and further our understanding of morpholino effects.